2021
DOI: 10.3390/jcm10153373
|View full text |Cite
|
Sign up to set email alerts
|

ADAM 17 and Epithelial-to-Mesenchymal Transition: The Evolving Story and Its Link to Fibrosis and Cancer

Abstract: For decades, metalloproteinase 17 (ADAM17) has been the goal of wide investigation. Since its discovery as the tumour necrosis factor-α convertase, it has been studied as the main drug target, especially in the context of inflammatory conditions and tumour. In fact, evidence is mounting to support a key role of ADAM17 in the induction of the proliferation, migration and progression of tumour cells and the trigger of the pro-fibrotic process during chronic inflammatory conditions; this occurs, probably, through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 116 publications
1
2
0
Order By: Relevance
“…Alterations in the cellular junction integrity lead to significant changes in salivary gland epithelial cells polarity and organization that may affect secretory functionality [ 19 ]. This scenario fits well with the inflammatory-related EMT activation program observed in SS, characterized by a loss of epithelial markers, such as E-cadherin and tight junction proteins [ 20 , 21 , 22 ]. All these phenomena, potentially implicated in the reduction of the normal quality and quantity of saliva in SS, resulted in accelerated development of SG inflammation [ 18 , 19 ].…”
Section: Sjögren’s Syndrome Featuressupporting
confidence: 81%
“…Alterations in the cellular junction integrity lead to significant changes in salivary gland epithelial cells polarity and organization that may affect secretory functionality [ 19 ]. This scenario fits well with the inflammatory-related EMT activation program observed in SS, characterized by a loss of epithelial markers, such as E-cadherin and tight junction proteins [ 20 , 21 , 22 ]. All these phenomena, potentially implicated in the reduction of the normal quality and quantity of saliva in SS, resulted in accelerated development of SG inflammation [ 18 , 19 ].…”
Section: Sjögren’s Syndrome Featuressupporting
confidence: 81%
“…In a previous study, profibrotic protein expression (e.g., TGF-β, CCN2) and airway fibrosis were suppressed in OVA-treated ADAM17 f/f /Cre + mice [ 51 ]. Moreover, TGF-β activates ADAM17, which in turn leads to the EMT via angiotensin-converting enzyme-2 ectodomain shedding or the RSK1/C/EBPβ pathway [ 50 , 52 ]. A Previous study found that AREG has a synergistic effect on TGF-β-induced EMT via Smad 2/3 pathway in fibroblasts [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…EMT is a key process in tumor progression. During EMT, epithelial tumor cells lose the epithelial cell hallmarks and acquire mesenchymal characteristics ( Zeisberg & Neilson, 2009 ), such as increased expressions of extracellular matrix (ECM) proteins and migratory properties ( Sisto, Ribatti & Lisi, 2021 ). N-cadherin (a cell adhesion molecule) and α-SMA (one of the cytoskeletal proteins) are mesenchymal marker proteins, which are considered important mediators in the EMT process and tumor cell migration ( Huang et al, 2021 ; Janthamala et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%